HUBUNGAN EKSPEKTASI KINERJA, EKSPEKTASI USAHA, DAN PENGARUH SOSIAL DENGAN PENERIMAAN MASYARAKAT DALAM PENGGUNAAN PUSKESMAS TANPA ANTRIAN KOTA SEMARANG (PUSTAKA) DI PUSKESMAS PONCOL SEMARANG - Irvine Nahla Anggraini; Septo Pawelas Arso; Rani Tiyas Budiyanti (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2021)
Poncol Health Center is one of the health center in Semarang City which has a high number of queues at the outpatient registration place, so this must be addressed immediately because it can affect patient satisfaction and impact the quality of health center services as well. In an effort to overcome this queuing problem, the Poncol Health Center implements the Puskesmas Tanpa Antrian Kota Semarang (PUSTAKA), namely outpatient registration via Whatsapp, SMS, or an application, that has been made by the Semarang Health Office. In its implementation, PUSTAKA has not been optimally utilized by patients, so this study aims to determine the factors which are associated with acceptance in the use of PUSTAKA program. This type of research is a quantitative research with a cross-sectional study design. The sample in the study amounted to 100 respondents who are users of PUSTAKA at Poncol Health Center. Data processing used univariate and bivariate analysis methods with the chi-square statistical test. The results of the study show that the variables which are significantly correlated to acceptance in the use of PUSTAKA program are performance expectancy (p=0,037) and effort expectancy (p= 0,015). The variable which is not significantly correlated is social influence (p= 0,434). Poncol Health Center are advised to optimizing the socialization of PUSTAKA, advise the Semarang Health Office to simplify the registration format, and provide another telephone number as an alternative for patients who have problems registering via SMS or Whatsapp